2022
DOI: 10.1111/jpim.12617
|View full text |Cite
|
Sign up to set email alerts
|

“Distance” in intellectual property protection and MNEs’ foreign subsidiary innovation performance

Abstract: The institutional environment surrounding firms is known to have a great impact on their innovation processes (Björk & Magnusson, 2009;Chesbrough, 2007). Multinational enterprises (MNEs) are increasingly innovating at foreign subsidiary locations having considerably different institutions from the MNE's home-base, and this increases the complexity in conducting innovation at subsidiary levels. Prior research suggests that in countries characterized by weak intellectual property (IP) protection, the threat of u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 133 publications
(202 reference statements)
0
1
0
Order By: Relevance
“…We argue here that this crucial gap in research is mainly because research has had a limited focus on the paradoxical nature of ID, or in other words, with the exception of the few (see Konara et al, 2022;Konara and Shirodkar, 2018), research has treated distance mainly symmetrically, disregarding how certain factors may offset any given influences simultaneously. To address this, based on the argument that in distant environments, the subsidiary's needs for engagement in local innovation activity increase (Bittencourt et al, 2017;Dunning and Lundan, 2008a, b), we argue that MNEs in certain host countries may assign their subsidiaries a certain level of autonomy to innovate, and this will offset the negative influences of formal ID.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…We argue here that this crucial gap in research is mainly because research has had a limited focus on the paradoxical nature of ID, or in other words, with the exception of the few (see Konara et al, 2022;Konara and Shirodkar, 2018), research has treated distance mainly symmetrically, disregarding how certain factors may offset any given influences simultaneously. To address this, based on the argument that in distant environments, the subsidiary's needs for engagement in local innovation activity increase (Bittencourt et al, 2017;Dunning and Lundan, 2008a, b), we argue that MNEs in certain host countries may assign their subsidiaries a certain level of autonomy to innovate, and this will offset the negative influences of formal ID.…”
Section: Introductionmentioning
confidence: 93%
“…Discussion, implications and limitations This study was motivated by the observation of increasing symmetry in ID research (Konara et al, 2022;Konara and Shirodkar, 2018), which ignores the paradoxical nature of ID, particularly in terms of the factors that offset the possible influences of formal ID. We challenge the assumption that formal ID can only have negative influences.…”
Section: Cross Cultural and Strategic Managementmentioning
confidence: 99%
“…Following recent developments in the literature with regard to the role, effect and treatment of institutional distance, we aim to extend our empirical analysis by joining the debate on direction of institutional distance (see e.g. Contractor, Yang and Gaur, 2016; Hernández and Nieto, 2015; Konara, Batsakis and Shirodkar, 2022). The aforementioned research has argued that the assumed symmetry in interpreting and estimating institutional distance has created an ongoing paradox, to a great extent unresolved, leading to spurious findings and inconsistent estimates.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Literature [11] in order to explore the effect of strategic IP sharing, proposed a game theory model to analyze the interaction between the degree of openness of the same-side platform, the absorptive capacity of the subject and the intensity of the network effect, which reveals the degree of competition of the open platform under the network effect. Literature [12] found that the distance of MNCs and the distance of the intensity of the host country's IP protection on the basis of the institution of intellectual property rights reduces the innovation capacity of MNCs in foreign subsidiaries and negatively affects the innovation performance of foreign subsidiaries through the study. Literature [13] adds a multi-supply environment to a multi-invention environment while incorporating the ecosystem to develop an IP strategy for a logistics network and a continuous and used IP strategy by combining the IP strategy with industry solutions through multi-IP protection.…”
Section: Introductionmentioning
confidence: 99%